Study of clinical profile of chronic kidney disease in non-diabetic patients - U., Ravi Kumar; J., Shashank; Swamy, Narayana (International Journal of Advances in Medicine, 2021)
Background: Chronic kidney disease (CKD) encompasses a spectrum of different pathophysiological processes associated with abnormal kidney function and a progressive decline in glomerular filtration rate. Cardiovascular disease is one of the major cause of morbidity and mortality in patients at every stage of CKD. Diabetes mellitus and hypertension together being major cause for CKD. Hypertension is a common cause for CKD and an independent risk factor for cardiovascular disease. This study mainly focused on the causes of CKD other than diabetes mellitus. An early detection and appropriate intervention of these patients will possibly help prevent progression of renal disease. Methods:We assessed 55 non diabetic CKD patients who presented to the OPD/IPD in Victoria hospital, Bowring and Lady Curzon hospital and other hospitals affiliated to Bangalore medical college and research institute during period June 2018 to December 2019. A detailed history and clinical examination was performed and patients were subjected to necessary investigations. Results: The commonest etiology for CKD was found to be hypertensive nephropathy followed by glomerulonephritis. Common symptoms were generalized weakness, lower limb swelling. Commonest signs are pallor, pedal edema and hypertension. Conclusions:CKD is a major health problem. Diabetic nephropathy is the commonest cause for CKD followed by hypertensive nephropathy and glomerulonephritis. Anaemia, pedal oedema, oliguria and generalised weakness were the major presenting clinical signs and symptoms in CKD. This condition when detected in early stages and managed can slow down the progression of CKDs and delay the need of renal replacement therapy.